Efektivitas Implementasi Peraturan Menteri Ketenagakerjaan Republik Indonesia Nomor 6 Tahun 2020 terhadap Hak Mahasiswa sebagai Peserta Pemagangan - Safina Callistamalva Arindrajaya; Devy Setiyani; Aris Prio Agus Santoso (Universitas Muhammadiyah Malang, 2021)
Universities develop academic pulpits both hard skills and soft skills by channeling students through internship programs. An internship program is conducted to prepare students in entering the world of work. Students as apprentices have rights that must be fulfilled by the apprentice operator based on The Minister of Manpower Regulation No. 6 of 2020 concerning the Implementation of Apprenticeships in the Country. But the fact that happened in the field still encountered apprentice organizers who do not fulfill the rights of students as apprentices. The apprenticeship operator instead employs students as apprentices with the capacity to work as permanent workers. This research was conducted to find answers to the formulation of problems on how to implement The Regulation of the Minister of Manpower of the Republic of Indonesia No. 6 of 2020 on students as apprenticeship participants and how effectively the implementation of The Minister of Manpower Regulation of the Republic of Indonesia Number 6 of 2020 on students as apprenticeship participants. This study uses qualitative descriptive research methods with a sociological juridical approach. The result of this study is the Regulation of the Minister of Manpower of the Republic of Indonesia Number 6 of 2020 concerning the Implementation of Apprenticeships in the Country is still not implemented perfectly in terms of fulfilling the rights of students as apprentices. In addition, the implementation of Regulation of the Minister of Manpower of the Republic of Indonesia Number 6 of 2020 concerning the Implementation of Domestic Apprenticeships on the rights of students as apprentices is still not effectively applied in the field. Abstrak Perguruan Tinggi mengembangkan akademik baik hard skill ataupun soft skill pada menyalurkan mahasiswa melalui program magang. Program magang dilakukan untuk menyiapkan mahasiswa dalam memasuki dunia kerja. Mahasiswa sebagai peserta pemagangan memiliki hak-hak yang harus dipenuhi oleh penyelenggara magang berdasarkan Peraturan Menteri Ketenagakerjaan Nomor 6 Tahun 2020 tentang Penyelenggaraan Pemagangan di Dalam Negeri. Namun fakta yang terjadi di lapangan, masih ditemui penyelenggara magang yang tidak memenuhi hak-hak mahasiswa sebagai peserta pemagangan. Penyelenggara magang justru mempekerjakan mahasiswa sebagai peserta pemagangan dengan kapasitas bekerja layaknya pekerja tetap. Penelitian ini dilakukan untuk menemukan jawaban dari rumusan masalah mengenai bagaimana implementasi Peraturan Menteri Ketenagakerjaan Republik Indonesia Nomor 6 Tahun 2020 pada mahasiswa sebagai peserta pemagangan serta bagaimana efektivitas implementasi Peraturan Menteri Ketenagakerjaan Republik Indonesia Nomor 6 Tahun 2020 pada mahasiswa sebagai peserta pemagangan. Penelitian ini menggunakan metode penelitian deskriptif kualitatif dengan pendekatan yuridis sosiologis. Hasil dari penelitian ini adalah Peraturan Menteri Ketenagakerjaan Republik Indonesia Nomor 6 Tahun 2020 tentang Penyelenggaraan Pemagangan Di Dalam Negeri masih belum terimplementasi secara sempurna dalam hal pemenuhan hak mahasiswa sebagai peserta pemagangan. Selain itu, implementasi Peraturan Menteri Ketenagakerjaan Republik Indonesia Nomor 6 Tahun 2020 tentang Penyelenggaraan Pemagangan Di Dalam Negeri terhadap hak mahasiswa sebagai peserta pemagangan masih belum efektif diterapkan di lapangan.